Assessing Green City-based Tree Cover Change in Nakhonratchasima City Municipality - Jantakat, Yaowaret; Juntakut, Pongpun (International Journal of Building, Urban, Interior and Landscape Technology, 2020)
Many cities has set goal of green city with tree increasing. The objective of this study is to assess green city-based tree cover change in Nakhonratchasima City Municipality (NCM). In analysis, Google Earth (GE) imagery during 2012-2020 was used for visual interpretation but the result of Urban Tree Canopy (UTC) cover interpretation on GE image in year 2020 only was evaluated accuracy in field and was used to be the base map for supporting GE photo-interpretation in the past (2012-2019). The result of annually UTC cover layers would be taken to estimate air pollutants ((CO, NO2, O3, PM10, M2.5 and SO2) via i-Tree Canopy on web. As results, the accuracy assessment of UTC cover map in year 2020 is 96.5517%. Tree cover change during the varying periods were found that there were ranged from dramatic reduction in percent tree cover of 17.2873% in year 2013 (because of built-up areas’ increasing in that time) and slight reducing 0.0561% in year 2015 to an increase in percent tree cover of 0.3122% in year 2016 and 0.0488% in year 2017 while percent tree cover has been gradually decreased between 2018 and 2020. At the same time, NCM’s UTC cover included the highest total removal value of CO (17.0 x 10-7 % per year) in year 2017; of NO2 (74.0 x 10-7 % per year) in year 2013, 2014 and 2017; of O3 (711.0 x 10-7 % per year) in year 2015; of PM10 (240.0 x 10-7 % per year) in year 2013 and 2014; of PM2.5 (38.0 x 10-7 % per year) in year 2017; of SO2 (48.0 x 10-7 % per year) in year 2013 and 2014. This assessment of such pollutant removal should not only be considered by tree cover but also the concerned factors (i.e., pollution concentrate, length of in-leaf season, amount of precipitation, and other meteorological variables). The mentioned results above, they will be used for spatial information for planning green city in area of NCM and guiding other green cities. Consequently, this study suggests for next work as: (1) study relationship between tree cover and land use/land cover and (2) study other related factors for UTC cover change.